2010
DOI: 10.1097/qai.0b013e3181e9e069
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Home and Clinic-Based HIV Testing Among Household Members of Persons Taking Antiretroviral Therapy in Uganda: Results From a Randomized Trial

Abstract: Home-based VCT for household members of HIV-infected persons was feasible, associated with lower prevalence, higher uptake, and increased identification of HIV-infected persons than clinic-based provision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(116 citation statements)
references
References 40 publications
5
111
0
Order By: Relevance
“…Coverage was reported in 19 home HTC studies 15,18,29–45 , one mobile 13 , two campaign 46,47 , three index partner/family member 4850 , five facility VCT 5155 , and five facility PITC studies 5661 . Overall, community HTC modalities achieved higher coverage than facility, with home (70%, 95% CI = 58–79) and campaign (76%, 95% CI = 49–95%) having the highest population coverage (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coverage was reported in 19 home HTC studies 15,18,29–45 , one mobile 13 , two campaign 46,47 , three index partner/family member 4850 , five facility VCT 5155 , and five facility PITC studies 5661 . Overall, community HTC modalities achieved higher coverage than facility, with home (70%, 95% CI = 58–79) and campaign (76%, 95% CI = 49–95%) having the highest population coverage (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Uptake was reported in 31 home HTC studies 5,14,15,18,27,2938,40–45,53,6274 , two home with self-testing 11,75 , two mobile 10,68 , three index partner or family member 4850 , four campaign 46,47,76,77 , three workplace 7880 , three facility VCT 54,56,81 , and 11 facility PITC studies 56,57,59,60,8187 . Overall, community modalities had high uptake (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…No contacts that we tested were found to be infected with HIV. Because access to household contacts, including family members and partners, has surfaced as one of the strengths of home-based HIV testing, 46 future studies should focus contact testing on high-risk household contacts and include in-depth qualitative data to understand HIV knowledge and factors influencing testing acceptance. Furthermore, as shown by our population's self-reported low use of condoms (77.3% reported never using condoms during sexual intercourse), future studies and interventions should also investigate cultural and socioeconomic factors influencing sexual practices and sexual risk behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Home-based HIV Counselling and Testing (HB-HCT) has been highly acceptable with improved HCT coverage and uptake in low and middle-income countries (Matovu et al 2006; Doherty et al 2013; Lugada et al 2010). A randomized controlled trial in Uganda comparing home-based and health facility testing found that 93 % of community members agreed to test in home sites; with 54.6 % of HIV infections identified compared to 27.3 % in villages with health facility-based HIV Counselling and Testing (HCT) (Yoder et al 2006).…”
Section: Results: Proposed Model To Enhance Treatment Accessmentioning
confidence: 99%